2006
DOI: 10.1128/mcb.26.9.3659-3671.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Regulates Pericentric Heterochromatin

Abstract: The retinoblastoma protein (pRb) has been proposed to regulate cell cycle progression in part through its ability to interact with enzymes that modify histone tails and create a repressed chromatin structure. We created a mutation in the murine Rb1 gene that disrupted pRb's ability to interact with these enzymes to determine if it affected cell cycle control. Here, we show that loss of this interaction slows progression through mitosis and causes aneuploidy. Our experiments reveal that while the LXCXE binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(174 citation statements)
references
References 61 publications
7
166
1
Order By: Relevance
“…In starvation experiments, observed in RB or RB silenced cells. 33,34,36,37 In this scenario, Hec1 overexpression may contribute to the reported capacity of pRb depleted cells to undergo chromosome missegregation as a consequence of defects in centromere/kinetochore structure that are responsible for kinetochore-microtubule misattachments, 38 such as merotelic attachments. 6,39 Consistently, recent work has demonstrated that loss of pRB causes centromere dysfunction associated with premature loss of centromeric cohesion, impaired localization of the condensin II subunit CAP-D3 to centromeres and formation of lagging chromosomes at anaphase.…”
Section: Methodsmentioning
confidence: 99%
“…In starvation experiments, observed in RB or RB silenced cells. 33,34,36,37 In this scenario, Hec1 overexpression may contribute to the reported capacity of pRb depleted cells to undergo chromosome missegregation as a consequence of defects in centromere/kinetochore structure that are responsible for kinetochore-microtubule misattachments, 38 such as merotelic attachments. 6,39 Consistently, recent work has demonstrated that loss of pRB causes centromere dysfunction associated with premature loss of centromeric cohesion, impaired localization of the condensin II subunit CAP-D3 to centromeres and formation of lagging chromosomes at anaphase.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, pRB-LXCXE interactions are critical for stress-responsive growth arrest, but not in reversible growth arrest or cell cycle arrest in development, even though each paradigm of proliferative control is pRB-dependent. 10,29,30 Notably, senescent Rb1 ΔL/ΔL MEFs can re-initiate DNA synthesis in response to ectopic E2F1 expression, whereas wildtype cells are resistant. 10 Furthermore, serially cultured Rb1 ΔL/ΔL MEFs escape senescence more readily than their wild-type counterparts, suggesting that defective silencing of proliferative genes can compromise the long-term stability of senescence arrest.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 We don't favor this interpretation, because our previous studies have indicated that HDACcontaining complexes interact with pRB in a GST-RB pull-down assay irrespective of the growth state of the cells. 29 Based on this line of reasoning, we expect that PML-pRB interactions are likely quite direct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular factors containing the LXCXE motif such as SWI/SNF complexes, DNMT1, Rbp2, and HDAC1/2 mediate transcriptional repression and chromatin regulation (21,24) by interacting with the LXCXE cleft located in the B subdomain (18) (see Fig. 1).…”
mentioning
confidence: 99%